2014
DOI: 10.1016/j.nmd.2014.06.441
|View full text |Cite
|
Sign up to set email alerts
|

Early onset and novel features in a spinal and bulbar muscular atrophy patient with a 68 CAG repeat

Abstract: Spinal and bulbar muscular atrophy (SBMA) is an X-linked neuromuscular disease caused by a trinucleotide (CAG) repeat expansion in the androgen receptor gene. Patients with SBMA have weakness, atrophy, and fasciculations in the bulbar and extremity muscles. Individuals with CAG repeat lengths greater than 62 have not previously been reported. We evaluated a 29 year old SBMA patient with 68 CAGs who had unusually early onset and findings not seen in others with the disease. Analysis of the androgen receptor gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…However, the age of disease onset correlates inversely with the CAG repeat length, i.e., greater CAG repeat lengths correspond to earlier disease onset [29]. Christopher Grunseich et al reported a 29-year-old patient with SBMA who had 68 CAG repeats in the AR gene and who had presented weakness since age 18 [14]. In our study, the father (II-2), 37 years old, had 53 CAG repeats (Fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, the age of disease onset correlates inversely with the CAG repeat length, i.e., greater CAG repeat lengths correspond to earlier disease onset [29]. Christopher Grunseich et al reported a 29-year-old patient with SBMA who had 68 CAG repeats in the AR gene and who had presented weakness since age 18 [14]. In our study, the father (II-2), 37 years old, had 53 CAG repeats (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…Spinal and bulbar muscular atrophy (SBMA; MIM 313200), also known as Kennedy's disease, is an Xlinked recessive and adult-onset motor neuron disease characterized by slowly progressive weakness and atrophy in the limb and bulbar muscles [13,14]. SBMA is caused by an expansion of trinucleotide cytosine adenine guanine (CAG) repeats in exon 1 of the androgen receptor (AR) gene on chromosome Xq11-12 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients affected with SBMA usually do not report symptoms that may suggest autonomic dysfunction; nevertheless, the subclinical involvement of both the orthosympathetic and parasympathetic nervous systems has been reported 39. Moreover, one single patient, carrying the longest CAG repeat ever found (68 triplets), reported autonomic dysfunctions such as decreased sweating and difficulties with ejaculation 4. In our SBMA cohort, we have studied Sympathetic Skin Response (SSR) and our preliminary findings are consistent with a prolonged latency of the potential (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…1 The AR CAG repeat ranges in size from 9 to 36 in healthy respondents but from 38 to 68 in patients with SBMA. [2][3][4] SBMA is characterised by loss of lower motor neurons in the spinal cord and brainstem, leading to progressive limb and bulbar muscle weakness and atrophy. SBMA affects adult males with onset usually between 30 and 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis of the disease is associated with an expansion of a CAG triplet repeat sequence, that codes for the amino acid glutamine (Q), located in exon 1 of the androgen receptor (AR) gene (La Spada, et al, 1991). In the normal population, this CAG repeat is comprised between 9 and 37 repeats (average=22), but in SBMA patients, expansions of more than 38 (up to 68) repeats (Fratta, et al, 2014a,Grunseich, et al, 2014a) results in disease. The CAG repeat codes for a polyglutamine (polyQ) tract, which is located in the N-terminal transactivation domain of the AR (ARpolyQ) protein.…”
Section: Sbma Is a Protein Misfolding Diseasementioning
confidence: 99%